Computed Tomography in Trauma Patients Accepted in Transfer:: Missed Injuries and Rationale for Repeat Imaging. Can we do Better? - Vernon, Seth A.; Helmer, Stephen D.; Ward, Jeanette G.; Haan, James M. (Kansas Journal of Medicine, 2019)
Introduction. Computed tomography scans often are repeated ontrauma patient transfers, leading to increased radiation exposure,resource utilization, and costs. This study examined the incidenceof repeated computed tomography scans (RCT) in trauma patienttransfers before and after software upgrades, physician education,and encouragement to reduce RCT.Methods.xThe number of RCTs at an American College of SurgeonsCommittee on Trauma verified level 1 trauma center was measured.The trauma team was educated and encouraged to use the computedtomography scans received with transfer trauma patients as perstudy protocol. All available images were reviewed and reasons for aRCT when ordered were recorded and categorized. Impact of systemimprovements and education on subsequent RCT were evaluated.Results. A RCT was done on 47.2% (n = 76) of patients throughoutthe study period. Unacceptable image quality and possible misseddiagnoses were the most commonly reported reasons for a RCT. Preventablereasons for a RCT (attending refusal to read outside films,incompatible software, and physician preference) decreased from25.8 to 14.3% over the study periods.Conclusions. The volume of unnecessary RCT can be reduced primarilythrough software updates and physician education, therebydecreasing radiation exposure, patient cost, and inefficiencies in hospitalresource usage. Kans J Med 2019;12(1):7-10.